The Legitimacy of Abortion: A Socio-Legal Analysis of Islamic Jurisprudence and Indonesian Law - Jalili, Ismail; Syaifuddin, Helmi; Ulfa, Fadillah; Gusmansyah, Wery; Zaim, Muntaha Artalim (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
Navigating the intersection of religious doctrines and legislative frameworks poses a significant challenge in the abortion discourse, particularly in Indonesia. This study investigates the legitimacy of abortion through the dual perspectives of Islamic jurisprudence and positive law within Indonesia’s intricate socio-cultural and religious milieu, where Islamic principles deeply influence legal interpretations and societal views. The study aims to dissect the complex legal and religious debates surrounding abortion in Indonesia, offering a thorough analysis of its legitimacy under both Islamic jurisprudence and state law. Current literature reveals a fragmented legal landscape marked by diverse interpretations and applications of Islamic principles and state laws, resulting in inconsistent legal outcomes. Adopting a qualitative methodology, this research utilizes doctrinal analysis of primary and secondary legal sources, statutory laws, judicial decisions, and Islamic legal texts. Findings highlight a stark dichotomy between strict prohibitions in traditional Islamic jurisprudence and more lenient, context-specific interpretations by contemporary scholars. The Indonesian legal system, heavily influenced by Islamic values, nonetheless displays flexibility in cases involving maternal health risks or severe fetal anomalies. Ultimately, this study advocates for a nuanced, context-sensitive legal framework that harmonizes Islamic jurisprudence with positive law. It proposes a balanced approach that respects religious values while addressing modern societal needs and medical realities, aiming to ensure legal clarity and safeguard women’s rights in Indonesia.